2020
DOI: 10.1177/0031512520918748
|View full text |Cite
|
Sign up to set email alerts
|

Positive Affective and Enjoyment Responses to Four High-Intensity Interval Exercise Protocols

Abstract: Several variables can be manipulated to compose high-intensity interval exercise (HIIE) protocols, and these different combinations may evoke different psychological responses (affect, enjoyment, mood, and perceived exertion). This study investigated psychological responses during four HIIE protocols. Following anthropometric measurements and two maximal exercise tests, 23 physically inactive adults (11 males [ Mage = 25.6, SD =  4.8 years; Mbody mass = 68.5, SD =  12.2 kg; Mheight = 1.72, SD =  0.08 m] and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 60 publications
(123 reference statements)
1
31
1
4
Order By: Relevance
“…It is interesting that affect valences immediately after exercise were positive (i.e., above 0) regardless of the oxygen environment in the current study. Based on data of previous studies carried out under normoxic condition, affect valences tended to reach the lowest point immediately post exercise [14,[33][34][35]. Some studies reported negative affect valences at the very end of SIT sessions [14,33], while results in other studies showed that affect valences remained positive [34,35].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is interesting that affect valences immediately after exercise were positive (i.e., above 0) regardless of the oxygen environment in the current study. Based on data of previous studies carried out under normoxic condition, affect valences tended to reach the lowest point immediately post exercise [14,[33][34][35]. Some studies reported negative affect valences at the very end of SIT sessions [14,33], while results in other studies showed that affect valences remained positive [34,35].…”
Section: Discussionmentioning
confidence: 93%
“…Based on data of previous studies carried out under normoxic condition, affect valences tended to reach the lowest point immediately post exercise [14,[33][34][35]. Some studies reported negative affect valences at the very end of SIT sessions [14,33], while results in other studies showed that affect valences remained positive [34,35]. Exercise intensity is a primary factor influencing affective responses in continuous training according to the dual-mode theory [22], yet affective responses to SIT with all-out effort could be influenced by other factors, for example, varied methodologies applied across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although our hypothesis of a favoring the long trial HIIE was rejected, our protocol was designed with support from a study that evaluated the peak-end rule in other context such as an aversion experience (Kahneman et al, 1993). Specifically, we followed Kahneman et al (1993) design and kept the same intensity over the short-trial because the effort accumulated over time induces an increase in RPE and a decrease in affect (Da Silva Machado et al, 2019;Frazão et al, 2016;Kellogg et al, 2019;Marques et al, 2020;Olney et al, 2018); thus, generating the worst values of psychological responses at the end of the trial (peak of intensity). Indeed, we added 50% duration with a gradual decrease in intensity in the long-trial, and although we did not find statistical differences for the global scales, 63.3% of participants found the shortest protocol the most intense protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, one article reported the results from three separate studies conducted in young healthy, inactive individuals ( n = 2; included) and middle-aged men with type 2 diabetes ( n = 1; excluded) (Songsorn et al, 2019 ). In total, n = 13 publications incorporating n = 18 unique observations were eligible and appropriate for meta-analysis [ Figure 2 ; (Wood et al, 2016 ; Townsend et al, 2017 ; Benítez-Flores et al, 2018 ; Good and Dogra, 2018 ; Niven et al, 2018 ; Olney et al, 2018 ; Bradley et al, 2019 ; Songsorn et al, 2019 ; Stork et al, 2019 ; Astorino et al, 2020 ; Marques et al, 2020 )]. We requested and received full individual participant data for all the eligible studies.…”
Section: Resultsmentioning
confidence: 99%
“…The majority employed acute designs with either a single SIE condition (Bradley et al, 2019 ; Astorino et al, 2020 ) or multiple conditions performed in a randomized order (Wood et al, 2016 ; Townsend et al, 2017 ; Benítez-Flores et al, 2018 ; Good and Dogra, 2018 ; Niven et al, 2018 ; Olney et al, 2018 ; Stork et al, 2018 ; Songsorn et al, 2019 ; Marques et al, 2020 ). The studies including multiple conditions either compared SIT to other exercise bouts (Wood et al, 2016 ; Good and Dogra, 2018 ; Niven et al, 2018 ; Olney et al, 2018 ; Stork et al, 2018 ; Songsorn et al, 2019 ), compared various SIE protocol permutations (Townsend et al, 2017 ; Benítez-Flores et al, 2018 ; Marques et al, 2020 ), or investigated the effect of music on the affective response to SIE (Stork et al, 2015 , 2019 ). In studies where the same participants completed different SIE protocol permutations in a cross-over design, each of the conditions were treated as an independent observation.…”
Section: Resultsmentioning
confidence: 99%